2021
DOI: 10.1016/j.ijid.2021.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical follow-up of patients suffering from moderate-to-severe COVID-19 infection: a monocentric prospective observational cohort study

Abstract: Long-term clinical follow up of patients suffering from moderate to severe COVID-19 infection: A monocentric prospective observational cohort study,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 46 publications
1
43
0
6
Order By: Relevance
“…Among the 193 studies under full-text review, 153 studies were excluded. Eventually, 40 studies were included in this meta-analysis based on the inclusion criteria [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The literature retrieval flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 193 studies under full-text review, 153 studies were excluded. Eventually, 40 studies were included in this meta-analysis based on the inclusion criteria [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. The literature retrieval flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 3 , 22 ] However, in these studies, as in our cohort, a significant improvement in DLCO was observed after six months. [ 3 , 23 , 24 ] Zhang et al reported a 32% reduction in DLCO after severe COVID-19 after eight months. In their cohort, 30% of patients had interstitial lung abnormalities, with ground glass being the most frequent (50%), followed by irregular lines.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 infection responsible for Coronavirus disease 2019 (COVID-19) is associated with a variability in clinical presentation and pathologic features, such as a minority of patients rapidly progressing to severe life-threatening respiratory failure requiring mechanical ventilation [ 1 ]. A proportion of COVID-19 patients suffer from post-acute sequelae, experiencing complications affecting different organs (a condition defined as “long COVID-19”, “long-haul” syndrome, or “post-acute COVID syndrome” (PACS) [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Most common symptoms often persisting for several weeks or months include systemic manifestations (fatigue, asthenia, poor concentration, wandering fever), symptoms and signs of pulmonary functional impairment (dyspnea, cough, reduced DLCO—diffusing capacity of the lungs for carbon monoxide), neuropsychiatric manifestations (sleep disturbances, cognitive dysfunction, depression, mood changes, anxiety, headache, taste, and/or smell loss), cardiac manifestations (chest pain, palpitations, tachycardia, dysrhytmias), as well as a variety of muscle-skeletal, renal, dermatological, and gastrointestinal manifestations [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%